(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes information about representatives of the literary environment of Bukhara contained in “Memoirs” of Sadriddin Aini. It is noted, that since the author himself was an active participant in the literary process in the Bukhara Emirate during the period under review, these materials serve as a reliable source in the study of the issue under consideration.